Uma abordagem de teste estrutural de uma transformações M2T baseada em hipergrafos - Abade, André da Silva (Universidade Federal de São Carlos, 2016)
Context: MDD (Model-Driven Development) is a software development paradigm in which the main artefacts are models, from which source code or other artefacts are generated. Even though MDD allows different views of how to decompose a problem and how to design a software to solve it, this paradigm introduces new challenges related to the input models, transformations and output artefacts. Problem Statement: Thus, software testing is a fundamental activity to reveal defects and improve confidence in the software products developed in this context. Several techniques and testing criteria have been proposed and investigated. Among them, functional testing has been extensively explored primarily in the M2M (Model-to-Model) transformations, while structural testing for M2T (Model-to-Text) transformations still poses challenges and lacks appropriate approaches. Objective: This work aims to to present a proposal for the structural testing of M2T transformations through the characterisation of input models as complex data, templates and output artefacts involved in this process. Method: The proposed approach was organised in five phases. Its strategy proposes that the complex data (grammars and metamodels) are represented by directed hypergraphs, allowing that a combinatorial-based traversal algorithm creates subsets of the input models that will be used as test cases for the M2T transformations. In this perspective, we carried out two exploratory studies with the specific purpose of feasibility analysis of the proposed approach. Results and Conclusion: The evaluation of results from the exploratory studies, through the analysis of some testing coverage criteria, demonstrated the relevance and feasibility of the approach for characterizing complex data for M2T transformations testing. Moreover, structuring the testing strategy in phases enables the revision and adjustment of activities, in addition to assisting the replication of the approach within different applications that make use of the MDD paradigm.
Keywords: Desenvolvimento dirigido a modelos; Modelo para texto; Transformações de modelos M2T; Teste em transformações de modelo; Teste estrutural; Dados complexos; Model-driven development; Model-to-text; M2T model transformations; Testing transformation model; Structural testing; Complex data; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO